Sistem Pengukuran Performa Human Resource Menggunakan Human Resource Scorecard: Studi Kasus di X Consulting - Salsabila Annisa Arista; Rehan Wira Widyatna; Erlinda Muslim (Business Management Journal, 2023)
Driven by today's rapid technological innovation, the world is changing at a breakneck speed. Business is one of the things that is greatly affected by this change, companies are required to continuosly improve and provide more value to customers compared to competitors by having strong Competitive Advantage (CA). 85% value of a company is based on intangible assets, which HR play a big role. The problem is, although the human resource is a very influential asset in a company, it is rarely considered and measured. In fact, Human Resources is one of the most important resource that each company should have. Therefore, this study aims to design a performance measurement system for human resources, so that it fits the company's goals and can be used as a tool for the HR division's report to X Consulting, a consulting firm where the value of this kind of company is really determined by the quality of its human resources. The design is carried out using the Human resource Scorecard method, based on the objectives, vision, mission, and values of the company, until a Key performance Indicator is generated for each strategic goal of each perspective (Financial, Customer, Operational, and Strategic). These KPIs were weighted using the Analytical Network Process and obtained 44 KPIs which were divided into 22 for leading indicators and 22 for lagging indicators.